Clinical experiences in the use of a gentamicin-coated titanium nail in tibia fractures - Schmidmaier, Gerhard (Injury, 2017)
Despite the improvement of surgical techniques surgical site infections (SSIs) still remain clinically challenging in high risk patients undergoing osteosynthesis for tibia fractures. The use of an antibiotic coated implant might reduce the adhesion of bacteria on the implant surface and could therefore reduce the rate of implant-related infection or osteomyelitis. A gentamicin-coated tibia nail was evaluated in a prospective study. Four centers enrolled 100 patients (99 treated) with fresh open or closed tibia fractures, or for non-union revision surgery and followed them for 18 months. Data collected included infection events, radiographs, SF-12, EQ-5D, Iowa Ankle score, and the WOMAC questionnaire. Sixty-eight of the 99 treated patients suffered from a fresh fracture, while in 31 patients, the intramedullary nail was implanted for revision purposes, including non-unions due to infection. Fifteen (22%) of the fresh fractures were GA Type III. The follow-up rate was 87% and 82% at 12 months and 18 months, respectively. Deep surgical site infections occurred in 3 fresh fractures and two in revision surgeries. We did not observe any local or systemic toxic effects related to gentamicin during this study. The use of the antibiotic coated nail is an option in patients with a high infection risk, like open factures or infected non unions, in the prevention of the onset of an implant-related infection or osteomyelitis.